The Curriculum of Islamic Education in Honoring Parents and its Method in The Noble Qur'an (Study of Analytical Interpretation in Surat Al-Isra verse 23-25 in The Interpretation of Al-Sha’rawy) - Junaidi, Junaidi; Pahrurroji, Pahrurroji; Huda, Ade Naelul (Proceeding of International Conference on Islamic Education (ICIED); Vol 9 No 1 (2024): Proceeding of International Conference on Islamic Education (ICIED)DO - 10.18860/icied.v9i1.3122, 2024)
This research aims to understand the thoughts of Muhammad Metwally Al-Shaarawy regarding the Islamic education curriculum's role in honoring parents. It also explores his interpretation of verses 23-25 in Surat Al-Isra and its relevance to contemporary reality. The main focus of this research was to analyze how Al-Shaarawy's interpretation of Surat Al-Isra verses 23-25 can be made understandable and applicable in real life for both scientists and non-scientists. The previous research has mainly focused on verses 23-24 and sometimes on 23-25. It attempts to explain that these verses address the issue of children without parents, but it fails to provide a method for teaching children about honoring their parents. The research also fails to establish whether the content of verses 23-25 serves as a curriculum for teaching children about honoring their parents. This study aims to supplement previous research by providing additional details about the educational process, drawing from Shaarawy's explanation of the verse. It further clarifies that the content of the verse serves as a method, as explained by Al-Shaarawy at the beginning of his commentary. This study is qualitative and descriptive, focusing on analyzing words, phrases, and sentences from the verses of the Holy Qur'an and interpreting them. The data sources include primary sources such as the Holy Qur'an and the interpretations of Muhammad Metwally Al-Shaarawy, as well as secondary sources such as hadith collections and their explanations, books of jurisprudence, relevant historical texts, and scientific journals related to the research . The research analyzed the Islamic education curriculum's approach to honoring parents, specifically focusing on Al-Shaarawy's interpretation of verses 23-25 of Surat Al-Isra. The research found that the curriculum emphasizes teaching faith in lordship and divinity, followed by worship, morals in both speech and action, self-purification, and the method of teaching through examples, stories, and proverbs. The application of this curriculum in contemporary reality is important for building the Muslim personality and promoting effective communication and empathy, starting with honoring and appreciating parents.